AGREEMENT IN DIAGNOSIS OF KNEE INJURIES BY ORTHOPEDISTS WITH CLINICAL EXPERIENCE IN KNEE TREATMENT - PROTTA,THIAGO ROCHA (2018)
ABSTRACT Objective: To analyze the level of agreement in diagnosing knee injury among orthopedists with clinical experience in knee treatment. Method: An online questionnaire was used to analyze the ability of orthopedic knee surgeons to diagnose intra-articular knee injuries using MRI, the importance given to this test in their clinical practice, and the agreement between these diagnoses and the radiology report. Results: The study participants considered MRI an important tool for clarifying inconclusive diagnoses and surgical planning. The level of agreement between the surgeons and the radiologist was considered to be very slight for posterior cruciate ligament injuries, collateral ligament injuries, and chondral injuries, and was considered slight for anterior cruciate ligament and meniscus injuries. Conclusion: A diagnosis of intra-articular knee injury must be based on the patient history, physical examination, and radiological imaging (MRI) in order to provide a complete approach to the patient. Level of Evidence III; Clinical study.